2016
DOI: 10.1016/j.jobcr.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical simvastatin (1.2mg) on gingival crevicular fluid interleukin-6, interleukin-8 and interleukin-10 levels in chronic periodontitis – A clinicobiochemical study

Abstract: CytokinesPeriodontal health GCF Host defence a b s t r a c tObjectives: The impact of simvastatin (SMV), a cholesterol lowering drug, on bone metabolism appears to involve complex interaction with cholesterol metabolites, hormones, inflammatory mediators and growth factors, thus having direct influence on extent and severity of periodontitis. The present study aims to evaluate the in vivo effect of subgingivally delivered SMV gel (1.2 mg) as a local drug-delivery agent on clinical parameters and on interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
1
28
2
1
Order By: Relevance
“…The increased knowledge on the inflammatory pathways involved in periodontitis has prompted the investigation of the effects of anti-inflammatory drugs as strategies to reduce gingival inflammation 16. Recent studies have suggested that cholesterol-lowering drugs such as simvastatin are protective against experimental2,4,17 and human periodontitis 18,19. These evidences have suggested that simvastatin is able to reduce bone loss and modulate the expression/release of inflammatory markers in gingival crevicular fluid samples.…”
Section: Discussionmentioning
confidence: 99%
“…The increased knowledge on the inflammatory pathways involved in periodontitis has prompted the investigation of the effects of anti-inflammatory drugs as strategies to reduce gingival inflammation 16. Recent studies have suggested that cholesterol-lowering drugs such as simvastatin are protective against experimental2,4,17 and human periodontitis 18,19. These evidences have suggested that simvastatin is able to reduce bone loss and modulate the expression/release of inflammatory markers in gingival crevicular fluid samples.…”
Section: Discussionmentioning
confidence: 99%
“…The flowchart of the literature search is presented in Figure 1. Out of 383 identified studies, 26 articles were selected for full-text review; 7 trials [25][26][27][28][29][30][31] were excluded for various reasons (Appendix S3).…”
Section: Study Selectionmentioning
confidence: 99%
“…The AG showed higher salivary IL-10 and IL-13 than the CG. IL-10 has been identified to be increased in the process of a hangover after alcohol consumption [66]. IL-10 has also been associated with the development of periodontitis [67].…”
Section: Discussionmentioning
confidence: 99%